Prokineticin 2 Plays a Pivotal Role in Psoriasis - He, Xiaoqin (EBioMedicine, 2016)
Psoriasis is histologically characterized by keratinocytes (KC) hyperproliferation, inflammation, and increased angiogenesis, but the pathological factor responsible for these symptoms is unknown. Here, a neuroendocrine peptide (prokineticin 2, PK2), is highly expressed in human and mouse psoriatic skins but no significant change in other autoimmune diseases, suggesting that PK2 is a psoriasis-specific factor. Bacterial products significantly up-regulated PK2, implying that infection induces PK2 over-expression. PK2 promoted KC and macrophage to produce interleukin-1 (IL-1), the central player of inflammation and psoriasis, which acts on adjacent fibroblast to induce inflammatory cascades and KC hyperproliferation. IL-1 feeds back on macrophages to induce PK2 production to perpetuate PK2-IL-1 positive feedback loop. PK2 also promoted angiogenesis, another psoriatic symptom. In mouse models, PK2 over-expression aggravated psoriasis while its knock-down inhibited pathological development. The results indicate that PK2 over-production perpetuates psoriatic symptoms by creating PK-2-IL-1 vicious loop. PK2 is a central player in psoriasis and a promising psoriasis-specific target.